Formative assessment of the communication skills related to drug delivery systems on standardized patients through group objective structured clinical encounters in second year medical students - Imran, Mohammed; Fatmi, Syed M.; Doshi, Chintan; Kharadi, Darshan (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Choosing an appropriate Drug Delivery System (DDS) influences the acceptability, adherence and better outcome of the therapy in the patients. The present study was planned to evaluate the second year MBBS students on standardized patients (SP) using Group Objective Structured Clinical Encounters (GOSCE) after content delivery by traditional power point class versus experiential teaching methodology. Methods: DDS practical class was held in two larger groups after adding two odd sub-groups (1+3) as ‘A’ (64 students) and even sub-groups (2+4) as ‘B’ (66 students). The formative GOSCE evaluation was done 2 weeks after the classes by the trained physician examiners as per the Medical Council of Canada pre-determined scoring instruments. Results: The average magnitude of change in GOSCE scoring is extremely statistical significant on t-test (P< 0.0001) in favour of experiential teaching methodology for all the skills. The statistical significant percentage of students were able to extract the treatment history in respect of eliciting problem, reasons for non-compliance, methods of intake, explain the technique and showed the courteous professional behaviours. Conclusions: The clinical cases as SP in pharmacology teaching for developing competency based communication skills and GOSCE are the appropriate methodology for evaluation of large student group for experiential DDS training.